A Proposal of Seismic Index for Existing Buildings in Indonesia using Pushover Analysis - Alex Kurniawandy; Shoji Nakazawa (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Indonesia has often suffered major earthquake damage over the past 50 years. There are thousands of buildings in earthquake-prone regions that still need seismic evaluation and rehabilitation. One method of evaluating the seismic performance of an existing building is by assessing it using the Japanese seismic index for structures. A basic seismic index can be calculated based on the strength and ductility criteria. The strength and ductility performance of a structure can be obtained by pushing a building until it reaches its maximum deformation capacity. This paper describes a proposal to obtain a basic seismic index using pushover analysis. Its adjustment to determine a seismic demand index by considering seismic hazard in Indonesia was carried out using the capacity spectrum method. Two existing buildings in Indonesia were evaluated. The evaluation result indicated that both buildings were in safe condition. The proposal of the seismic index method can be useful in determining the performance index of existing structures. The ductility index can also be used to estimate the response modification factor of a structure.